2017
DOI: 10.1007/s00464-017-5771-y
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral totally extraperitoneal (TEP) repair of the ultrasound-diagnosed asymptomatic contralateral inguinal hernia

Abstract: Bilateral TEP for the clinically unilateral groin hernia with an occult contralateral groin hernia can be performed without increased morbidity, accepting a minor and very temporary impairment of QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…[ 12 ] found that among all patients undergoing unilateral TEP, seven patients developed inguinal hematoma and four patients developed edema of cord and those undergoing bilateral TEP, three were developed inguinal hematoma and one developed edema of cord. In a study conducted by Malouf et al .,[ 9 ] complication rate in unilateral TEP patients was 6.8% and in patients who were diagnosed to have COH on USG and underwent bilateral TEP, complication rate was 13% which was comparable. This study is having better postoperative clinical outcomes than that of studies conducted by Chiang et al .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…[ 12 ] found that among all patients undergoing unilateral TEP, seven patients developed inguinal hematoma and four patients developed edema of cord and those undergoing bilateral TEP, three were developed inguinal hematoma and one developed edema of cord. In a study conducted by Malouf et al .,[ 9 ] complication rate in unilateral TEP patients was 6.8% and in patients who were diagnosed to have COH on USG and underwent bilateral TEP, complication rate was 13% which was comparable. This study is having better postoperative clinical outcomes than that of studies conducted by Chiang et al .…”
Section: Discussionmentioning
confidence: 80%
“…[ 8 ] sensitivity and specificity of USG for detection of inguinal hernia were 96.6% and 84.4%, respectively. In a similar study conducted by Malouf et al .,[ 9 ] 34.6% patients with a clinically unilateral hernia had COH on preoperative ultrasonographic assessment and all of them accepted to go for repair of both defects in same setting. In this study, it was found that all three patients had occult hernia on left side; however, Bochkarev et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Também houve forte associação entre a formação de hematomas e a bilateralidade, o que pode ser justificado pela dissecção mais ampla, em comparação com a hérnia unilateral 15 .…”
Section: Discussionunclassified